Gaseous and Electrochemical Hydrogen Storage Properties of Mg-Based Thin Films - Xin, Gongbiao (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
In this thesis, the author introduces the preparation of a series of Mg-based thin films with different structures by magnetron sputtering, and the systematical investigation of their gaseous and electrochemical hydrogen storage properties under mild conditions. The promising applications of Mg-based thin films in smart windows, hydrogen sensors and Ni-MH batteries are also reviewed. The research work presented in this thesis offers significant perspectives on the research of Mg-based hydrogen storage materials, especially the Mg-based films. Moreover, the unique experimental procedures and methods (including the electric resistance, optical transmittance and electrochemical methods) used in this thesis can also provide valuable reference for the researchers in the field of Mg-based hydrogen storage films.